Da liberdade à falta de reconhecimento : aposentadoria e saúde mental de professoras e professores universitários - Genuino, Elaine Milena Alves (2024)
This dissertation aims to analyze the relationship between retirement and the mental health of university professors from public institutions who have retired from their classroom practices. To this end, qualitative research was conducted with fifteen retired university professors, using two instruments: a sociodemographic questionnaire and a semi-structured interview. The content analysis method with thematic cuts was employed to analyze the material produced in the research. From this stage, three central categories were identified: I. Specificities of university teaching work; II. Experience of Retirement; and III. Retirement and health. Based on these categories, the articles composing this dissertation were produced, all theoretically grounded in the Psychodynamics of work. Thus, Article I aimed to characterize retired university professors' understandings of teaching work. Article II aimed to investigate the repercussions of retirement on the lives of university professors. And Article III aimed to identify how retired university professors understand the relationship between health and retirement. Overall, the results obtained in the studies indicate the factors present in retirement that can result in individuals' mental illness. Among the main elements are the lack of recognition in retirement, the impacts of this phase on individuals' identities, the context in which retirement was implemented, leisure due to the absence of work activity, gender issues and socially attributed roles to femininity, loss of social status provided by work, entering the aging phase, and lack of retirement planning.